Exchange-spring like magnetic behavior of the tetragonal Heusler compound Mn2FeGa as a candidate for spin-transfer torque - Gasi, Teuta; Nayak, Ajaya K.; Winterlik, Juergen; Ksenofontov, Vadim; Adler, Peter; Nicklas, Michael; Felser, Claudia (Applied Physics Letters, 2013)
We report structural, magnetic, and Mössbauer studies of the Heusler compound Mn2FeGa. Theoretical calculations predict that a tetragonal phase in Mn2FeGa could be an interesting candidate for spin torque transfer applications due to the presence of perpendicular magnetic anisotropy. Experimentally, we found that Mn2FeGa crystallizes in a tetragonal structure after annealing at low temperatures (≤ 400 ° C), whereas, it becomes pseudocubic for higher annealing temperatures. The sample annealed at 400 °C shows a high Curie temperature of 650 K and a hard-magnetic behavior. We observed a nonsaturating and exchange-spring type of hysteresis loops, which indicates that the sample contains two different magnetic states. The Mössbauer measurements clearly support the structural and magnetic data. All these properties make the material a potential candidate for spintronic devices, especially in thin films with perpendicular magnetic anisotropy. © 2013 AIP Publishing LLC.
CRIS-Team Scopus Importer:2023-03-20